Infertility misperception and improper health-seeking behavior between urban and rural areas - Berli Kusuma; Achmad Kemal Harzif; Mila Maidarti; Yudianto Budi Saroyo; Hariyono Winarto; Alfa Putri Meutia (PLoS ONE, 2025)
Objectives The prevalence of infertility among reproductive-age couples in Indonesia is around 10-15%. Lack of understanding, misleading myths, and negative attitudes could result in improper behavior. This study aims to reveal the discrepancy between perception and behavior towards infertility in urban and rural areas in Indonesia. Materials and methods A cross-sectional study using an internet-based questionnaire was given to 408 individuals, divided into two groups, Java and outside Java, representing urban and rural populations. The study included Indonesian citizens over 18 who were willing to participate, encompassing individuals of both genders, regardless of their fertility status. All participants completed the questionnaire from October 2020 to April 2021. Results Half of the respondents from both groups consider infertility a disease. All respondents have excellent access to information. Although more than 80% of subjects from each group had been exposed to infertility information, a better understanding was observed in the urban community. Most subjects answered that smoking is the leading risk factor for infertility, followed by stress and advanced age. More respondents in rural areas have the wrong perception that stress causes infertility. Furthermore, they seek unwarranted advice, as 19.5% came to midwives and only 9.1% came to general practitioners. This study showed that 35.6% of subjects in the urban group and 41.6% in the rural group are considered late to seek healthcare assistance. Most respondents from both groups accept using Assisted Reproductive Technology and fertility-enhancing drugs as treatment options. Conclusion Infertility misconceptions are more prevalent in rural groups than in urban groups. Fertility education among both groups needs to be improved to optimize the chance of conceiving and having a healthy baby.